Do Organization Engagement and Commitment have a role in Turnover Intention? - Dwita Darmawati; Rio dhani Laksana; Intan Shaferi; Ilkay Aydogmus (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2025)
Human resource practices play a critical role in influencing employee behavior and organizational outcomes, particularly in reducing turnover intention through increased organizational commitment and engagement. The goal of this study is to determine how human resource practices which include career management, compensation satisfaction, performance evaluation, individual job fit, and work control affect turnover when organizational commitment and engagement are used as interventions. With 330 employees from Syariah Hotels in Purwokerto as the whole population or test used, this consideration fits into the causal-comparative inquiry kind. The SPLS software application is used for information analysis. Out of the twelve proposed hypotheses, six were supported. Organizational commitment was significantly influenced by person-job fit and performance appraisal, while organizational engagement was significantly influenced by career management and performance appraisal. The remaining hypotheses were not supported, potentially due to contextual factors such as employee perception of HR practices, uneven implementation across departments, or demographic characteristics that moderated the expected effects. Additionally, organizational engagement and commitment characteristics may affect turnover. This study found that both organizational commitment and engagement significantly mediate the relationship between HR practices and employees' turnover intention, highlighting the importance of fostering a committed and engaged workforce to reduce turnover rates.